2020
DOI: 10.7554/elife.62514
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism for direct actin force-sensing by α-catenin

Abstract: The actin cytoskeleton mediates mechanical coupling between cells and their tissue microenvironments. The architecture and composition of actin networks are modulated by force, but it is unclear how interactions between actin filaments (F-actin) and associated proteins are mechanically regulated. Here, we employ both optical trapping and biochemical reconstitution with myosin motor proteins to show single piconewton forces applied solely to F-actin enhance binding by the human version of the essential cell-cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 91 publications
(126 reference statements)
4
93
0
Order By: Relevance
“…Actin-binding proteins have also been shown to modulate filament structural conformations either as part of their regulatory activity or as a means for allosteric cooperative binding to actin 30 32 . In addition to effects of protein binding, mechanical perturbations to actin filaments such as torques, tension 33 , 34 and bending have been suggested to influence protein interactions with filaments, including the binding activity of the Arp2/3 complex 21 and severing activity of the protein cofilin 20 , 35 , 36 . Together, these observations suggest that different conformations of F-actin, induced either mechanically or biochemically, could impact the affinity of actin-binding proteins for F-actin.…”
Section: Introductionmentioning
confidence: 99%
“…Actin-binding proteins have also been shown to modulate filament structural conformations either as part of their regulatory activity or as a means for allosteric cooperative binding to actin 30 32 . In addition to effects of protein binding, mechanical perturbations to actin filaments such as torques, tension 33 , 34 and bending have been suggested to influence protein interactions with filaments, including the binding activity of the Arp2/3 complex 21 and severing activity of the protein cofilin 20 , 35 , 36 . Together, these observations suggest that different conformations of F-actin, induced either mechanically or biochemically, could impact the affinity of actin-binding proteins for F-actin.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that this region is flexible and in various conformations. Recently, the cryogenic electron microscopy structure to 2.9 Å resolution was reported of MVt residues 879–1134 bound to F-actin, but the N-terminus residues 879–980 that include the first α-helix (that we originally named H1’ to emphasize its distinction from the equivalent α-helix H1 of the vinculin isoform) of this five-helix bundle were disordered and could not be modeled [ 70 ]. This is consistent with an earlier 8.2 Å reconstruction of MVt (residues 858–1129) that also showed that α-helix H1’ was displaced from the five-helix bundle domain [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfolding of the vinculin tail domain upon binding to filamentous actin or acidic phospholipids has been suggested before [ 15 ], resulting in the release of the coiled coil region preceding α-helix H1’ (or α-helix H1 in vinculin). The recent electron microscopy structures of the F-actin binding domains of vinculin, metavinculin, or αE-catenin have their first α-helices released from their five-helix bundles as a consequence of binding to F-actin as documented by the isolated F-actin binding domains bound to the actin filament [ 70 , 73 ]. Our cryogenic electron microscopy structure of human full-length metavinculin provides a first glimpse of the α-helix H1’ being released even within the auto-inhibited state as a part of its conformational flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central 3 four-helix bundles form the middle (M)-region that functions as a mechanosensor ( 20 , 21 , 22 , 23 , 24 , 25 ). The C-terminal five-helix bundle forms the F-actin-binding domain (ABD) ( 11 , 13 , 26 , 27 ). F-actin binding is allosterically regulated: αE-catenin can bind F-actin readily as a homodimer, but when in complex with β-catenin, mechanical force is required for strong F-actin binding ( 9 , 10 , 11 , 26 ).…”
mentioning
confidence: 99%